PENGARUH PERTUMBUHAN EKONOMI DAN PENINGKATAN PARTISIPASI WANITA BEKERJA TERHADAP UPAYA MENURUNKAN TINGKAT FERTILITAS DI KABUPATEN BOJONEGORO - Eka Adiputra; Ria Septiani (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
China has succeeded in reducing the birth rate from 2.63 children per woman to 1.61 children per woman in 2009. It turns out that factors affecting the decline in birth rate (TFR) is not only due to government policy, economic factors and the number of women's participation also have a major effect on the decrease of TFR. The purpose of this research is to analyze the effect of economic growth and the participation of working women on the birth rate (TFR). The results of this study are economic growth and the participation of working women has no effect on the birth rate. This is because the factors of working women who affect the birth rate occurs only in big cities or metropolis whereas Bojonegoro regency is categorized as an agricultural area that has not become a metropolis.